Hyphessobrycon rutiliflavidus n. sp., a new characid fish from the upper rio Paraguai, State of Mato Grosso, Brazil (Characiformes: Characidae) - Carvalho, Fernando Rogério (2008)
Hyphessobrycon rutiliflavidus, new species, is described from the upper rio Paraguai in Cuiaba, State of Mato Grosso, Brazil. The new species differs from all other congeners by the following combination of characters: black humeral spot, slightly diffuse at its tips, and caudal-peduncle blotch present; midlateral body stripe conspicuous in its posteriormost portion, extending to the tips of the middle caudal rays; anal fin with iii, 15 to iv, 19 rays (mode iv, 17); upper jaw length, 42.3 to 49.5% of the head length; maxilla with 2-5 teeth (mode 3); all the fins of males reddish-orange and of females yellowish. Copyright © 2008 Magnolia Press.